Perubahan Balungan Lampahan dalam Pakeliran Wayang Kulit Purwa Gaya Surakarta - Junaidi Junaidi; Bayu Aji Suseno (Institut Seni Indonesia Yogyakarta, 2020)
The Changes on Balungan Lampahan in Pakeliran of Purwa Puppet of Surakarta Style.This research aims to increase the appreciation of the shadow puppet purwa pakeliran according to the times and society. Balungan lampahan as the basic framework, is static and never to be changed, but then it is dynamic and full of changes. The method used is descriptive comparative, while data analysis is based on the structure theory of the wayang play by Alton L. Becker and Arnold Hauzer's social change. The results can be found in three forms of balungan lampahan namely: (1) overnight, (2) compact, and (3) solid. Change is partial and total due to changes in the society that supports wayang, namely as the art of royal ritual traditions (monarchy and ritualism) turning into modern art and entertainment (modern and profane). Thus, the change in balungan lampahan represents changing times and society, so it needs to be appreciated by the puppeteers for the pakeliran.Keywords: changes; balungan lampahan; pakeliran; shadow puppets; Surakarta style